A Dose-Ranging Study of 0.5% Bupivacaine or Ropivacaine on the Success and Duration of the Ultrasound-Guided, Nerve-Stimulator–Assisted Sciatic Nerve Block: A Double-Blind, Randomized Clinical Trial. Issue 6 (1st November 2013) - Nader, Antoun; Kendall, Mark C.; De Oliveira, Gildasio S.; Puri, Lalit; Tureanu, Luminita; Brodskaia, Alina; Asher, Yogen; Parimi, Vamsi; McCarthy, Robert J.
Abstract : Background and Objectives: Before bifurcation, the sciatic nerve is composed of 2 component nerves encased in a common investing extraneural layer (CIEL). We examined the effect of various volumes injected beneath the CIEL on the success and duration of sciatic nerve block. Methods: Ultrasound-guided nerve-stimulator–assisted sciatic nerve blocks were performed on 142 subjects. Subjects were randomized into 14 groups (0.5% ropivacaine or bupivacaine) with epinephrine 1:300, 000 in volumes ranging from 2.5 to 30 mL. Successful block was defined as a complete sensory and motor block at 60 minutes. The minimum threshold current, time to complete block, duration of sensory and motor block, postoperative pain, and analgesic requirements were recorded. Results: The mean threshold current external to the CIEL was 0.52 (0.15) mA compared to 0.19 (0.09) mA beneath the CIEL ( P < 0.001). Successful block was achieved in 30 of 40 subjects that received 5 mL or less of ropivacaine or bupivacaine compared with 97 of 99 that received 10 mL or greater volume ( P = 0.006). Injection volumes greater than or equal to 10 mL produced complete sensory and motor block within 30 minutes. Volumes greater than 10 mL did not extend the duration of the sensory or motor block. Injection volumes of 2.5 and 5 mL were associated with delayed onset and decreased block duration and a greater fraction of subjects experiencing pain behind the knee. Conclusions: Injecting 10 mL of 0.5% bupivacaine or ropivacaine below the CIEL produces comparable onset and duration of sensory and motor blockade as volumes as large as 30 mL.